KEEFEKTIFAN PENERAPAN PADUAN MODEL PEMBELAJARAN PROBLEM SOLVING DAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA KELAS XI IPA - Devita Sulistiana (Center of Language and Cultural Studies, 2016)
The objective of this study is to see effectiveness of problem solving and cooperative learning model in teaching sciences for SMA students, implementing quasy experiment posttest only. The study assigned three groups of students: 42 for problem solving treatments, another 42 for cooperative STAD, and 39 for integration of problem solving-cooperative of STAD. Instrument of the study consisted of observation guide, essay test, and questionnaire. This study discovered: (1) Students who were taught using cooperative problem solving model achieved better attainment than those who received individual problem solving model. (2) Students using critical thinking in the problem solving model performed worse than those who received cooperative-model of STAD type. (3) Implementation of problem solving-cooperative model of STAD type gives better achievement than cooperative of STAD type.